Evaluation of geothermal energy extraction in Enhanced Geothermal System (EGS) with multiple fracturing horizontal wells (MFHW). (May 2020) - Gong, Facheng; Guo, Tiankui; Sun, Wei; Li, Zhaomin; Yang, Bin; Chen, Yimei; Qu, Zhanqing
Abstract: The deep geothermal energy produced from Enhanced Geothermal System (EGS) has a great development prospect because of enormous potential and environmental friendliness. EGS process involves a complex thermal-hydraulic process, and fractures in EGS are main channels for fluid flow and heat transfer, the understanding of which is crucial to the sustainable utilization of geothermal reservoirs. In this paper, a 3D thermal-hydraulic coupled numerical model is proposed to describe the interaction of fluid flow and heat transfer. Besides, the EGS with multiple fracturing horizontal wells (MFHW) is adopted to evaluate the effect of multiple hydraulic fractures on geothermal energy extraction performance. The MFHW with multiple stimulated fractures could increase fluid flow path and heat exchange area significantly, thereby enhance the heat recovery ability. Firstly, we analyzed the evolution of temperature and flow fields in EGS and compared the MFHW EGS with conventional vertical EGS. Secondly, the effects of fracturing parameters, including the fracture number, fracture length, and fracture conductivity, on heat extraction performance were investigated. Finally, the cost for drilling and hydraulic fracturing in MFHW EGS was calculated. The results indicate that MFHW EGS has a higher cumulative thermal production and a better heat extraction performance than that of conventional vertical EGS. For the optimization of hydraulic fracture parameters, the cumulative thermal production firstly increases and then decreases as the fracture number increases, the cumulative thermal production curve exists an inflection point of fracture number. Longer fracture length and higher fracture conductivity could enhance the cumulative thermal production, but the output growth slows down gradually. Considering economic cost, the best fracture parameters for MFHW EGS in this paper are the fracture number of 7, the fracture length of 300 m, and the fracture conductivity of 350 μm 2 cm, respectively. The research provides a better study for multiple fracturing horizontal wells (MFHW) EGS and helps to optimize fracture parameters and geothermal reservoir management, which is conductive to improve the geothermal energy efficiency. Highlights: An EGS with multiple fracturing horizontal well (MFHW) was put forward. A 3D MFHW thermal-hydraulic coupled model was established. The MFHW EGS was compared with conventional vertical EGS. The optimal fracture parameters for MFHW EGS were concluded.